RESEARCH OF THE MARKET OF DAIRY PRODUCTS OF UKRAINE - Стахурська, Світлана В. (Journal of Strategic Economic Research, 2023)
The presented work examines the main trends of the modern development of the dairy market in Ukraine. The main development trends and opportunities have been identified. On the dairy market, there is a gradual increase in the production of milk and dairy products. This is due to the expansion of livestock complexes, improvement of technologies and increase in productivity of animals. The purpose of the presented work is research and analysis of the latest trends in the development and possibilities of risk reduction in the market of dairy products in Ukraine. The research methods are analysis and synthesis to determine the main vectors of the development of the dairy market in Ukraine, induction and deduction, a graphic method for visual presentation of research results. Ukraine is actively developing the export of dairy products to foreign markets. The demand for Ukrainian dairy products is growing, and this stimulates the development of production and the improvement of product quality. Therefore, there is a growing demand for organic dairy products in Ukraine. Consumers are increasingly paying attention to the quality of products and their impact on health, which contributes to the development of the organic sector. An important element of the development of the dairy products market is the creation of a positive image of Ukrainian dairy brands both on the domestic and foreign markets. This stimulates the trust of consumers and partners. The development of dairy processing allows the production of more types of dairy products and expands the assortment for consumers. This contributes to the growth of production volumes and market development. The introduction of innovative technologies in the production of dairy products allows to increase the efficiency of production, reduce costs and increase the quality of products. Adherence to international standards of product quality and safety is becoming more and more important for competitiveness on the dairy market. All these trends contribute to the development of the dairy products market in Ukraine and create new opportunities for producers, exporters and consumers. Ensuring the sustainable development of this market requires the attention of economists, scientists and production owners.